Aspek-aspek perilaku keberagamaan dalam masyarakat perspektif Al-Qur’an dan teori sosial - Rohmah, Hasna’ Naili; Jannah, Ismawatul; Atho’illah, Ahmad Zen; Roibin, Roibin (Maliki Interdisciplinary Journal, 2024)
Religious behavior in society not only reflects the dimensions of individual spirituality, but also reflects its relationship with social theory which studies social structure and dynamics. In the Indonesian context, various forms of religious behavior such as mystical, mythical, puritanical, ritual, secret and profane show their own variations and characteristics. This article highlights the importance of understanding and appreciating this diversity as Indonesia’s cultural richness. The social theory approach helps in exploring the meaning and function of each religious behavior. For example, mystical behavior explores deep spiritual dimensions, while ritual behavior expresses respect for religious traditions and values. However, this diversity should not be a reason to blame each other, but rather an opportunity to enrich our understanding of diversity in society. In the Qur’an, there are verses that highlight the wisdom of diversity, emphasizing the importance of respecting differences to achieve peace and harmony. This article proposes the need for an inclusive approach in managing religious diversity, promoting harmony between religious communities, and building a society that respects and maintains the richness of cultural diversity.